ANALYSIS OF MECHANISMS FOR TOLERATING MULTIPLE LINK FAILURES IN MPLS NETWORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Multiprotocol Label Switching (MPLS) is switching network and provides significant benefits by fast forwarding packets. MPLS is scalable network and it is useful for end-to-end quality of service (QoS), it also enabling efficient utilization of existing network resources. In MPLS, there is no admission control for nodes and it is connection-oriented network which makes network more reliable. For MPLS network, failure can be occur at any point of time if the network link is overloading with traffic or node leave network. If the link failure occur in the MPLS network then there is need to establish a new label switched path (LSP) and then forward the packets to the newly established LSP. The forwarding of failed link traffic to different or backup path this may leads LSP get more congested. Here some mechanisms used for to tolerate these link failures in MPLS network. The main focus to analyze the various mechanisms used for tolerates the link failure in MPLS based on the Quality of Service (QoS) parameters. The expected result from this thesis, the network should maintain connectivity after multiple failures without causing congestion.